Analysis of TIP Articles in the Ferienjob Case: The Role of International Institutions and Humanitarian Organizations (Discourse Journal on Law and Society, 2025)
Ferienjobs are part-time jobs done during holiday periods, and are not a form of internship but rather a part of the job market. The Ferienjob case in Germany underlies the application of the Human Trafficking Crime article because this practice is detrimental and violates human rights. The research methodology used is a normative juridical approach. The aim of this research is to determine the elements that underlie the application of the Human Trafficking Crime article in the Ferienjob case as well as the role of international institutions in the issue of human trafficking crimes.